3D visualization and quantification of microvessels in the whole ischemic mouse brain using solvent-based clearing and light sheet microscopy. Issue 10 (October 2017) - Lugo-Hernandez, Erlen; Squire, Anthony; Hagemann, Nina; Brenzel, Alexandra; Sardari, Maryam; Schlechter, Jana; Sanchez-Mendoza, Eduardo H; Gunzer, Matthias; Faissner, Andreas; Hermann, Dirk M
The visualization of cerebral microvessels is essential for understanding brain remodeling after stroke. Injection of dyes allows for the evaluation of perfused vessels, but has limitations related either to incomplete microvascular filling or leakage. In conventional histochemistry, the analysis of microvessels is limited to 2D structures, with apparent limitations regarding the interpretation of vascular circuits. Herein, we developed a straight-forward technique to visualize microvessels in the whole ischemic mouse brain, combining the injection of a fluorescent-labeled low viscosity hydrogel conjugate with 3D solvent clearing followed by automated light sheet microscopy. We performed transient middle cerebral artery occlusion in C57Bl/6j mice and acquired detailed 3D vasculature images from whole brains. Subsequent image processing, rendering and fitting of blood vessels to a filament model was employed to calculate vessel length density, resulting in 0.922 ± 0.176 m/mm 3 in healthy tissue and 0.329 ± 0.131 m/mm 3 in ischemic tissue. This analysis showed a marked loss of capillaries with a diameter ≤ 10 µm and a more moderate loss of microvessels in the range > 10 and ≤ 20 µm, whereas vessels > 20 µm were unaffected by focal cerebral ischemia. We propose that this protocol is highly suitable for studying microvascular injury and remodeling post-stroke.